Visualization of Arabidopsis root system architecture in 3D by refraction-contrast X-ray micro-computed tomography. (30th July 2021) - Kurogane, Tomofumi; Tamaoki, Daisuke; Yano, Sachiko; Tanigaki, Fumiaki; Shimazu, Toru; Kasahara, Haruo; Yamauchi, Daisuke; Uesugi, Kentaro; Hoshino, Masato; Kamisaka, Seiichiro; Mineyuki, Yoshinobu; Karahara, Ichirou
Abstract: Plant roots change their morphological traits in order to adapt themselves to different environmental conditions, resulting in the alteration of the root system architecture. To understand this mechanism, it is essential to visualize the morphology of the entire root system. To reveal effects of long-term alteration of gravity environment on root system development, we have performed an experiment in the International Space Station using Arabidopsis plants and obtained dried root systems grown in rockwool slabs. The X-ray computed tomography (CT) technique using industrial X-ray scanners has been introduced to visualize the root system architecture of crop species grown in soil in 3D non-invasively. In the case of the present study, however, the root system of Arabidopsis is composed of finer roots compared with typical crop plants and rockwool is also composed of fibers having similar dimension to that of the roots. A higher spatial resolution imaging method is required for distinguishing roots from rockwool. Therefore, in the present study, we tested refraction-contrast X-ray micro-CT using coherent X-ray optics available at the beamline of the synchrotron radiation facility SPring-8 for bio-imaging. We have found that a wide field of view but with low resolution obtained at the experimental Hutch 3 of this beamline provided an overview map of the root systems, while a narrow field of view but with high resolution obtained at the experimental Hutch 1 provided an extended architecture of the secondary roots, by a clear distinction between roots and individual rockwool fibers, resulting in the successful tracing of these roots from their basal regions.